Application of the concept of a virtual competitive window for predicting the bandwidth of the Wi-Fi wireless segment - Ченлян, Інь; Лазебний, В. С. (Problems of Informatization and Control, 2017)
It was proposed some expressions to calculate the probabilistic parameters of the data transmissionprocess using the Wi-Fi wireless network. The calculations was done for data streams transmitted byusing TCP and UDP protocols. The results of the collision impact assessment on the bandwidth of the Wi-Fi network with competitive access are presented